THE DRIVERS OF EMPLOYEE ENGAGEMENT AMONG KNOWLEDGE WORKERS IN TERTIARY EDUCATION IN CHINA WITH THE MODERATOR OF CURIOSITY: A CONCEPTUAL PAPER - Tang, Xiao; Yip, Foon Yee (INTI International University, 2022)
Employee engagement is a key factor for an organization’s success and competitive advantage. The engagement level of knowledge workers in tertiary education determines the efficiency and quality of tertiary education, as well as the healthy and sustainable development of tertiary education. However, China's overall employee engagement level is very low, and specific to the knowledge workers in the field of tertiary education is also not optimistic. And the low engagement will lead to many problems, such as poor performance, health complaints (burnout, depressive symptoms, sleep disturbances), stress and strains, and intention to quit This study examines the factors that influence and shape employee engagement of the knowledge workers in the context of tertiary education in China. It does this by studying multilevel factors at three levels, the individual, organizational and external levels. The present study will investigate the influence of the organizational culture, perceived supervisory support, and new ways of working on employee engagement among knowledge workers in the tertiary education area in China. And also investigate whether curiosity moderates the relationship between organizational culture, perceived supervisory support, and new ways of working to the employee engagement among knowledge workers in tertiary education in China. A questionnaire was used to collect data from the respondents while Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to test the study hypotheses.